HOGG1 polymorphism in atrophic gastritis and gastric cancer after Helicobacter pylori eradication - Sun, Lei-Min (Baishideng Publishing Group Co., Limited, 2010)
AIM: To investigate the association between Ser326Cys human oxoguanine glycosylase 1 (hOGG1) polymorphism and atrophic gastritis and gastric cancer after Helicobacter pylori (H. pylori) eradication. METHODS: A total of 488 subjects (73 patients with gastric cancer, 160 with atrophic gastritis after H. pylori eradication and 255 controls) were prospectively collected. Polymerase chain reaction-restriction fragment length polymorphism analysis was performed to distinguish hOGG1 Ser326Cys polymorphism. Statistical analysis was conducted by two-sample t test for continuous variables and χ(2) test for categorical variables. Logistic regression models were used to find the risk factors for gastric cancer and atrophic gastritis. RESULTS: Neither the hOGG1 Ser/Cys nor the Cys/Cys genotype was associated with gastric cancer. Compared with the Ser/Ser genotype, odds ratio (OR) for Ser/Cys was 0.96, (95% CI: 0.51-1.84) and OR for Cys/Cys was 1.1 (95% CI: 0.48-2.1). No association was detected between hOGG1 polymorphism and Lauren type of gastric cancer (P = 0.61) either. However, Ser/Cys and Cys/Cys were significantly associated with atrophic gastritis with OR: 1.76 for Ser/Cys (95% CI: 1.03-3.0) and 2.38 for Cys/Cys (95% CI: 1.34-4.23). After controlling for age, gender, smoking and alcohol, there were still significant associations with OR: 2.05 for Ser/Cys (95% CI: 1.14-3.68) and 2.76 for Cys/Cys (95% CI: 1.47-5.18). CONCLUSION: HOGG1 polymorphisms (Cys/Cys and Ser/Cys) are associated with atrophic gastritis. No significant association is detected between hOGG1 polymorphisms (Cys/Cys or Ser/Cys) and gastric cancer.